College Football Revival: Analyzing the Impact of Marketing Efforts on Key Stakeholders at a Division I FCS Commuter School - Lucas A. Christiansen; Amanda Greene; Charles W. Jones (Journal of Applied Sports Management, 2019)
The current study examined the impact of a recently restarted football program and a new on-campus stadium on the alumni and students of a Division I FCS commuter school. Results showed that alumni felt more connected to the university because of the new football program, they were more satisfied with their overall game-day experience, and the new football stadium was more likely to increase their game attendance when compared to students. Supplementary analysis highlights key differences in how each group rated individual elements of the game-day experience and the mediums used by each group for obtaining team-related information. Subscribe to JASM
Keywords: Collegiate athletics; commuter schools; game-day experience; sense of community; stakeholder theory